A Periodic Collaboration and Coexistence Management Model with the Oscillation Effect for Complex Mega Infrastructure Project under the Risk of Infection. (2nd October 2018) - Zhao, Na; Cheng, T. C. E.
Abstract : In view of the intergroup structural relationships involved with the complex mega infrastructure projects (MIP), we develop a periodic collaboration and coexistence model that can efficiently curb the risk of infection and ensure normal, orderly progress. We conduct a systematic analysis of the periodic collaboration and the coexistence process for mega infrastructure projects. The results suggest that when a complex major engineering project develops the risk of infection and one group keeps expanding, assimilation or disappearance of the other group may occur, impeding the normal project construction process. If a disruption occurs, it is difficult to resume construction, and substantial economic losses can result. Furthermore, the periodic collaboration and coexistence management model with the oscillation effect can effectively prevent the risk of problems from spreading among groups. By doing so, the model stabilizes the intergroup structural balance in a complex major engineering system. In summary, our model and analysis help, to some extent, to elucidate the critical mechanisms influencing the risk of infection in engineering collaborative management and explain the collaboration and coexistence rules for a complex mega infrastructure project that may risk spreading infection to other parts of the project. The research findings, while further verifying and supplementing relevant theories, also provide beneficial references for collaborative management practices.